A Review of Scheduling Strategies for Radiotherapy and Immune Checkpoint Inhibition in Locally Advanced Rectal Cancer - Lydia Melissourgou-Syka; Michael A. Gillespie; Sean M. O'Cathail; Owen J. Sansom; Colin W. Steele; Campbell S. D. Roxburgh (Journal of Immunotherapy and Precision Oncology, 2023)
Colorectal cancer (CRC) is the third most common malignancy across the globe and, despite advances in treatment strategies, survival rates remain low. Rectal cancer (RC) accounts for most of these cases, and traditional management strategies for advanced disease include total neoadjuvant therapy (TNT) with chemoradiotherapy followed by curative surgery. Unfortunately, approximately 10–15% of patients have no response to treatment or have recurrence at a short interval following radiotherapy. The introduction of immunotherapy in the form of immune checkpoint blockade (ICB) in metastatic colorectal cancer has improved clinical outcomes, yet most patients with RC present with microsatellite stable disease, which lacks the immune-rich microenvironment where ICB is most effective. There is evidence that combining radiotherapy with ICB can unlock the mechanisms that drive resistance in patients; however, the sequencing of these therapies is still debated. This review offers a comprehensive overview of clinical trials and preclinical models that use radiotherapy–immunotherapy combinations in RC in an attempt to extrapolate the ideal sequencing of the two treatment modalities. The results highlight the dearth of evidence to answer the question of whether ICB should be given before, during, or after radiotherapy, yet it is suggested that improving the relevance of our preclinical models will provide a platform with higher translational value and will lead to appropriate clinical trial designs.